2008
DOI: 10.1002/eji.200838521
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells and viral immunity

Abstract: Langerhans cells (LC) are a unique dendritic cell subset that are located in mucosal stratified squamous epithelium and skin epidermis. Their location is ideally suited for their function as antigen presenting cells that capture invading viruses and induce anti-viral immunity. However, it is becoming evident that the interaction between LC and viruses can result in different responses, depending on the virus and the receptors involved. Here we will discuss the recent data on the similarities and differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 88 publications
2
51
1
Order By: Relevance
“…Recent evidence suggests that langerin 2 dDCs and langerin + dDCs are the cutaneous DC subsets that present viral Ag to naive T cells postinfection of murine skin (22,41). LCs are the major APCs in the epidermis and so are likely to be the first DC subset to encounter HSV, because this infection is first confined to the epidermis, but their role in the immune response to acute HSV skin infection remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that langerin 2 dDCs and langerin + dDCs are the cutaneous DC subsets that present viral Ag to naive T cells postinfection of murine skin (22,41). LCs are the major APCs in the epidermis and so are likely to be the first DC subset to encounter HSV, because this infection is first confined to the epidermis, but their role in the immune response to acute HSV skin infection remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection of the mucosal tissues, HSV encounters a variety of cells, including dendritic cells (DCs), that bridge innate and adaptive immunity (7). Immature DCs are able to capture and process viral antigens.…”
mentioning
confidence: 99%
“…In the skin, LCs are the obvious primary DC subset likely to be initially involved in HSV-1 antigen uptake, and, accordingly, earlier analyses on the role of LCs in anti-HSV-1 immunity claimed that depletion of LCs before infection leads to increased HSV-1 virulence (Sprecher and Becker, 1986). However, more recently, several studies have conclusively shown that in WT mice, LCs are not the cells presenting HSV-1 antigens to CD8 + T cells and thus are not directly involved in the induction of MHC class I-restricted antiviral immune responses (Allan et al, 2006;Cunningham et al, 2008;Bedoui et al, 2009;Eidsmo et al, 2009;Puttur et al, 2010). After epicutaneous HSV-1 infection, lymph noderesident CD8α + DCs or migratory CD103 + dermal DCs were identified to be the predominant DC population presenting HSV-1 antigens to CD8 + T cells (Allan et al, 2006;Bedoui et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, although LCs are the primary cutaneous antigen-acquiring cells it has been shown that lymph node-resident DCs but not LCs induce MHC class I-restricted antiviral immunity and the priming of HSV-1-specific CTLs (Allan et al, 2003;Cunningham et al, 2008;Bedoui et al, 2009), most likely because HSV-1-infected LCs appeared to be compromised in their trafficking ability as they failed to downregulate E-cadherin or undergo apoptosis after HSV-1 infection (Bosnjak et al, 2005;Eidsmo et al, 2009;Cunningham et al, 2010;Puttur et al, 2010).…”
Section: Introductionmentioning
confidence: 97%